Implementation of Experimental Methods in Improving the Science Skills of Children Aged 5-6 Years - Sumartin Sumartin; Ferdian Utama; Yuning Eka Rahma Wati (Bulletin of Early Childhood, 2025)
This research is motivated by the importance of developing science skills in early childhood US the base for critical thinking, creativity, andproblem solving, while science learning in Early Childhood Education still tends to be theoretical and does not involve direct children'sexperiences. This study aims to describe the implementation of experimental methods in improving the science skills of children aged 5-6 years atMa'arif 28 Mountain Adi Kindergarten for the 2025/2026 Academic Year, with a focus on aspects of planning, implementation, and evaluation oflearning. The research method used is a qualitative approach with a descriptive type, through data collection techniques in the form of observations, interviews, and documentation of school principals, teachers, and 12 children US research subjects. The results of the study showthat the application of experimental methods is able to improve children 's science skills US a whole, including exploratory activities, the ability tosolve simple problems, creative attitudes, understanding cause and effect, and the ability to classify and sort objects. Children become more active,enthusiastic, and confident in participating in learning because they are directly involved in experimental activities. In addition, the success of thismethod is supported by the role of teachers in providing guidance, the use of varied media, and interactive and fun learning. Thus, experimentalmethods have proven to be effective in developing early childhood science skills and can be an alternative to innovative learning strategies in earlychildhood education.